The epidemiology, management, and the associated burden of migraine in Australian primary care: a retrospective analysis of electronic health record data - Nicole Limberg; Jason C. Ray; Benjamin Harvey; Giles Stratton; Angus Cuskelly; Charmaine S. Tam; David Witcombe (The Journal of Headache and Pain)
Abstract Background Migraine accounts for more disability than all other neurologic conditions combined. Despite this, more than 40% of people with migraine do not seek medical care. Migraine is associated with a higher risk of comorbidities, adding to the symptom burden. Currently, there is limited epidemiological data available on the prevalence and incidence of migraine in the Australian primary care setting. This study aimed to describe the epidemiology (prevalence and incidence) of diagnosed migraine within the Australian general practice population. Methods Electronic health record data captured by national clinical practice management software over a 14-year index period (2010–2024) was analysed. The point prevalence of diagnosed migraine was estimated. The incidence of diagnosed migraine was estimated based on patients with new onset migraine during the index period. Estimates were stratified by age and sex. Differences by sociodemographic groups, patterns of treatment, and referral pathways were also evaluated. Results The study encompassed a total of 37,579 eligible migraine prevalent cases. The overall adjusted point prevalence of diagnosed migraine was estimated as 7.02 per 1,000 persons (95% confidence interval (CI) 6.79 to 7.25), which equates to 0.702% after adjusting for the interaction of age and sex. The overall incidence rate (IR) was estimated as 3.48 per 1,000 person-years (95% CI 3.38 to 3.58) after adjusting for the interaction of age and sex. Depression and anxiety were reported four times more frequently in the migraine population. High use of opioids and opioid combinations (54.75%) was noted in the migraine population, as well as a lower-than-expected use of triptans (51.06%). Among those with migraine, 32.03% had been referred to a physiotherapist and 18.64% had been referred to a neurologist. Conclusions This is the first study to describe the IR, accounting for life-years, in the Australian general practice population. The point prevalence of diagnosed migraine and incidence were lower than population-based estimates from other regions. The findings indicate that migraines are frequently underdiagnosed in the Australian primary care setting, with a possible lack of awareness of potential presentations for migraine, including neck pain, and highlight the need for further patient and clinician education.